2000
DOI: 10.1103/physrevc.62.054909
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic transverse flow and the quark-hadron phase transition

Abstract: We use ͑3ϩ1͒-dimensional hydrodynamics with exact longitudinal boost invariance to study the influence of collision centrality and initial energy density on the transverse flow pattern and the angular distributions of particles emitted near midrapidity in ultrarelativistic heavy-ion collisions. We concentrate on radial flow and the elliptic flow coefficient v 2 as functions of the impact parameter and collision energy. We demonstrate that the finally observed elliptic flow is established earlier in the collisi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

35
782
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 561 publications
(819 citation statements)
references
References 68 publications
35
782
2
Order By: Relevance
“…The hadron transverse momentum anisotropy is generated by the pressure anisotropy in the initial compressed matter formed in noncentral heavy-ion collisions [2,3] and is sensitive to the properties of produced matter in these collisions. For heavy-ion collisions at the Relativistic Heavy Ion Collider (RHIC), it has been shown that this sensitivity exists not only in the larger elliptic flow [4][5][6][7][8][9][10][11] but also in smaller higher order anisotropic flows [12][13][14][15][16][17][18]. To investigate the influence of initial collision geometry on anisotropic flows in heavy-ion collisions, one usually varies the impact parameter of a collision or the atomic number of colliding nuclei [19].…”
Section: Introductionmentioning
confidence: 99%
“…The hadron transverse momentum anisotropy is generated by the pressure anisotropy in the initial compressed matter formed in noncentral heavy-ion collisions [2,3] and is sensitive to the properties of produced matter in these collisions. For heavy-ion collisions at the Relativistic Heavy Ion Collider (RHIC), it has been shown that this sensitivity exists not only in the larger elliptic flow [4][5][6][7][8][9][10][11] but also in smaller higher order anisotropic flows [12][13][14][15][16][17][18]. To investigate the influence of initial collision geometry on anisotropic flows in heavy-ion collisions, one usually varies the impact parameter of a collision or the atomic number of colliding nuclei [19].…”
Section: Introductionmentioning
confidence: 99%
“…To simulate central Au+Au collisions at RHIC, we use the standard initialization described in [31] and provided in the downloaded AZHYDRO input file [32], corresponding to a peak initial energy density of ε i = 30 GeV /f m 3 at τ i = 0.6 f m/c. Since we are exploring the equation of state dependence on the splitting of the away side jet, we assume a simple equation of state, p(ε) = c 2 s ε, with ε(T ) = π 2 30 g q T 4 , g q = 47.5.…”
Section: Hydro+jet Modelmentioning
confidence: 99%
“…For the hydrodynamic evolution we use a modified version of the publicly available hydrodynamic code AZHY-DRO [31,32]. The code is formulated in (τ, x, y, η) coordinates, where τ = √ t 2 −z 2 is the longitudinal proper time, η= 1 2 ln t+z t−z is space-time rapidity, and r ⊥ = (x, y) defines the plane transverse to the beam direction z. AZHYDRO employs longitudinal boost invariance along z but this is violated by the source term (4).…”
Section: Hydro+jet Modelmentioning
confidence: 99%
“…We use the equation of state EOS-Q described in [7,16] incorporating a first order phase transition and hadronic chemical freeze-out at a critical temperature T c = 164 MeV. The hadronic sector of EOS-Q is soft with a squared speed of sound c 2 s ≈ 0.15.…”
mentioning
confidence: 99%
“…To simulate central Au+Au collisions at RHIC, we use the standard initialization described in [7] and provided in the downloaded AZHYDRO input file [16], corresponding to a peak initial energy density of ε 0 = 30 GeV/fm 3 at τ 0 = 0.6 fm/c. We use the equation of state EOS-Q described in [7,16] incorporating a first order phase transition and hadronic chemical freeze-out at a critical temperature T c = 164 MeV.…”
mentioning
confidence: 99%